Linguistic and Psychological Problems in English Speaking Among Eighth-Grade Students - Rafli Arnanda Amin Nurrohman; Alief Noor Farida (Universitas Muhammadiyah Barru, 2026)
This study aims to examine the linguistic and psychological problems faced by eighth-grade students in speaking English at SMP Negeri 2 Semarang. This study employs a descriptive qualitative research design with a case study approach. The participants were 32 eighth-grade students for classroom observation, while 10 students were selected for semi-structured interviews through purposive sampling. Data were collected through classroom observations and interviews and analyzed using the interactive model of data analysis, including data condensation, data display, and conclusion drawing. The findings reveal that students experience two main categories of speaking problems. The linguistic problems include limited vocabulary, inaccurate grammar usage, and poor pronunciation. The psychological problems consist of fear of making mistakes, anxiety, shyness, and lack of self-confidence. Among these problems, limited vocabulary and fear of making mistakes are the most dominant factors affecting students’ speaking performance. These findings indicate that speaking difficulties are influenced by both linguistic and psychological factors. Therefore, teachers are recommended to apply vocabulary support activities, confidence-building speaking tasks, and interactive communicative strategies to improve students’ speaking ability.